Três décadas de austeridade fiscal no Brasil - Santos, Francyelle do Nascimento (2021)
This paper aims to analyze the Brazilian experience with fiscal austerity, which has been in force in the country for three decades. It seeks to show that the concept of austerity predominated in Brazil's macroeconomic policy throughout this period, as well as to debate the transformations of the Brazilian State generated by the imposition of the Washington Consensus on Latin American countries, to which the Brazilian governments of the 1990s committed to follow. In this sense, it is a work that walked through the history of neoliberalism and the origins of austerity in economic theory, but also through the Brazilian economy, seeking to identify the consequences of austere policies on economic indicators. The proposal, both theoretically and empirically, was to carry out a broad approach, considering different analytical approaches and macroeconomic variables. In order to do so, there is a debate on neoliberalism and its influence on economic policy; austerity in economic theory; the historical context in which fiscal austerity gains hegemony in international economic policy; as well as the transformations of the Brazilian State, from the last decade of the last century, and the effects of austerity on the country's economic development. Regarding the performance of the Brazilian economy and the role of the State in this context, the analysis was carried out from two perspectives: the development strategy and the macroeconomic policy. Finally, the main mechanisms of fiscal austerity in Brazil were analyzed, namely: The Fiscal Responsibility Law; the Public Debt and the Spending Ceiling. In methodological terms, we seek to dialogue with the Marxian dialectic. Among other aspects, the choice of dialectical historical materialism is justified by having among its principles the understanding that there is always an interdependence between phenomena and that their appearance does not coincide with their essence. We understand fiscal austerity as a complex phenomenon that involves economic, political, legal, social and ideological elements, whose narrative is very different from the socioeconomic consequences it engenders, so we consider this methodological approach, attentive to the contradictory movement that characterizes the development of the phenomenon, pertinent. In the case of the Brazilian experience, the analysis indicates that the change in the development strategy, therefore in the role of the State, was a sine qua non for the adoption of fiscal austerity policies. So, in Brazil, auterity is not just a dangerous idea, but materializes in macroeconomic management, especially in fiscal policy. In this sense, it is found that, through different mechanisms, austerity has been institutionalized as a State policy, not just governments, and that its effects are harmful to the Brazilian economy and society, but consistent with the purposes of a process of capital accumulation led by financial capital, which is not based on national economic growth.